2015
DOI: 10.1136/thoraxjnl-2015-206938
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of COPD in never-smokers and ever-smokers in the general population: results from the CanCOLD study

Abstract: NCT00920348 (ClinicalTrials.gov); study ID number: IRO-93326.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
137
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(153 citation statements)
references
References 33 publications
14
137
1
1
Order By: Relevance
“…Participants between 45 and 90 years from the multisite, population-based CanCOLD study were evaluated [12,13] ; the sites include Vancouver, Calgary, Ottawa, Quebec City, Montreal, Toronto, Halifax, Kingston, and Saskatoon. Ethics approval was obtained from the institutional review board at each CanCOLD study site.…”
Section: Participantsmentioning
confidence: 99%
“…Participants between 45 and 90 years from the multisite, population-based CanCOLD study were evaluated [12,13] ; the sites include Vancouver, Calgary, Ottawa, Quebec City, Montreal, Toronto, Halifax, Kingston, and Saskatoon. Ethics approval was obtained from the institutional review board at each CanCOLD study site.…”
Section: Participantsmentioning
confidence: 99%
“…Smoking is the most frequent cause of COPD, although there are other risk factors such as exposure to occupational dust, air pollution and biomass burning. 20 We observed that 42% of our patients reported exposure to wood stoves.…”
Section: Results As N (%) or ± Sd (Min-max)mentioning
confidence: 83%
“…18 COPD underdiagnosis results in late recognition of the disease and in later stages. 19,20 Early detection of airflow limitation and smoking cessation intervention may delay the decline of lung function, reduce COPD symptoms, and improve the patient's quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, those with low TLCO ventilated in excess of the prevailing metabolic demand, i. e. they had poorer exertional ventilatory efficiency (figure 1a). Early emphysema [5], ventilation distribution heterogeneity [10] and pulmonary microvascular disease [6], in different combinations, could explain these findings, particularly in subjects susceptible to the deleterious effects of smoking. The physiological basis of these derangements likely stem from increased dead space per se rather than a small tidal volume [11].…”
Section: To the Editormentioning
confidence: 99%
“…It is noteworthy that a low TLCO has been linked to structural markers of early emphysema [5] and pulmonary microvascular abnormalities [6] in smokers with airflow limitation but preserved forced expiratory volume in 1 s (FEV1), i.e. Global Initiative for Chronic Obstructive Lung Disease (GOLD) stage 1.…”
Section: To the Editormentioning
confidence: 99%